2018
DOI: 10.1093/brain/awy021
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain and oligoclonal bands are prognostic biomarkers in radiologically isolated syndrome

Abstract: The prognostic role of cerebrospinal fluid molecular biomarkers determined in early pathogenic stages of multiple sclerosis has yet to be defined. In the present study, we aimed to investigate the prognostic value of chitinase 3 like 1 (CHI3L1), neurofilament light chain, and oligoclonal bands for conversion to clinically isolated syndrome and to multiple sclerosis in 75 patients with radiologically isolated syndrome. Cerebrospinal fluid levels of CHI3L1 and neurofilament light chain were measured by enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 18 publications
3
86
1
Order By: Relevance
“…In patients with Alzheimer disease and amyotrophic lateral sclerosis, increasing mean serum concentrations occur months or years before the emergence of the first clinical manifestations. 35,36 Similarly, an increased CSF NfL concentration in radiologically isolated syndrome is a risk factor for later transition to clinically definite MS. 37,38 Recent results from clinical trials in progressive MS accord with those in relapsing-remitting disease (table 1) and suggest that the concentration of NfL is associated with concurrent disease activity and long-term disease outcome in all forms of MS. In placebo-controlled phase 3 trials of fingolimod and siponimod, baseline plasma NfL concentrations were higher in patients with Gd+ lesions at baseline compared with those without Gd+ lesions.…”
Section: Clinical Validitymentioning
confidence: 82%
“…In patients with Alzheimer disease and amyotrophic lateral sclerosis, increasing mean serum concentrations occur months or years before the emergence of the first clinical manifestations. 35,36 Similarly, an increased CSF NfL concentration in radiologically isolated syndrome is a risk factor for later transition to clinically definite MS. 37,38 Recent results from clinical trials in progressive MS accord with those in relapsing-remitting disease (table 1) and suggest that the concentration of NfL is associated with concurrent disease activity and long-term disease outcome in all forms of MS. In placebo-controlled phase 3 trials of fingolimod and siponimod, baseline plasma NfL concentrations were higher in patients with Gd+ lesions at baseline compared with those without Gd+ lesions.…”
Section: Clinical Validitymentioning
confidence: 82%
“…NFL seems to be a robust marker of ongoing disease activity in pwMS. Moreover, NFL levels correlate well with conversion to clinically definitive MS [15,16], increased number of relapses, confirmed disability worsening, treatment and MRI outcomes [17], spinal cord and brain atrophy [4,18,19], and different clinical forms such as radiologically isolated syndrome [20], clinically isolated syndrome (CIS) ( [21], relapsing-remitting MS (RRMS) [16,22,23], and primary progressive MS (PPMS) [24]. NFL levels correlate significantly with the presence of gadolinium enchancing lesions and T2 lesion load [20].…”
Section: Discussionmentioning
confidence: 97%
“…It has been found that a higher CSF NfL concentration is an independent risk factor for the development of MS in RIS patients, although it has minor relevance (hazard ratio = 1.03, 95% CI 1.01-1.05 p = 0.003) in comparison to other prognostic markers such as CSF IgG oligoclonal bands (OCB) (hazard ratio = 8.9, 95% CI 1.04-75.6 p = 0.046). [39] The ability of CSF NfL to predict conversion to MS in CIS patients is controversial. While some authors have reported higher CSF NfL values at the baseline in CIS patients who were later diagnosed with MS,[S8] some others have reported contrasting findings.…”
Section: Nfl In the Monitoring And Prognostic Evaluation Of Multiple mentioning
confidence: 99%